Case study on subcontracting arrangements in the scaffolding supply chain of a Liquefied Natural Gas infrastructure project - Lopez, Robert; Chong, Heap-Yih; Moon, Sungkon; Wang, Xiangyu (Journal of Civil Engineering and Management, 2017)
The objective of the study presented in this paper is to determine the characteristics of the scaffolding supply chain in a liquefied natural gas (LNG) infrastructure project. This research is significant as the outsourcing of scaffolding is integral to its use and productivity toward LNG infrastructure project completion. As such, this paper presents the research undertaken on the subcontracting of scaffold manufacturing, supplying and delivering. It focuses upon the organisations, management and control in scaffolding subcontracting. A comparative analysis of three organisations was carried out to reveal issues with current practice in manufacturing, supplying and delivering scaffold products for assembly onsite. Their management and control approaches are also compared and contrasted. It is found that, while the divided contract approach may help save costs, enhance market exposure and is ideal when choice of subcontractor is limited, its risks can impact upon the entire project and be difficult for the contractor to control. The limited background in scaffolding studies and importance of subcontracting within LNG infrastructure projects has made this research timely. This paper identifies issues in relation to quality assurance, warranties and rework, which have the potential to mitigate any cost benefits obtained from subcontracting practices within this supply chain.